2018
DOI: 10.1021/acsami.8b00990
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermi Level Alignment with Tin Oxide on the Hysteresis of Perovskite Solar Cells

Abstract: We tune the Fermi level alignment between the SnO electron transport layer (ETL) and Cs(FAMA)Pb(IBr) and highlight that this parameter is interlinked with current-voltage hysteresis in perovskite solar cells (PSCs). Furthermore, thermally stimulated current measurements reveal that the depth of trap states in the ETL or at the ETL-perovskite interface correlates with Fermi level positions, ultimately linking it to the energy difference between the Fermi level and conduction band minimum. In the presence of dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 28 publications
5
72
0
Order By: Relevance
“…The residual hysteresis in our devices after optimization of perovskite quality is attributed to the surface traps, which is also consistent with slow increase of photocurrent observed in current–time ( I – t ) scan shown in Figure S9 of the Supporting Information . It was also reported that the hysteresis is related to the energy level alignment at ETL/perovskite interface, which in turn is affected by the presence of deep trap states . In addition to the reduction in the interface trap density, improvements in the conductivity of SnO 2 may also contribute to reduced hysteresis .…”
Section: The Summary Of Parameters Of Devices and Films For Differentsupporting
confidence: 84%
“…The residual hysteresis in our devices after optimization of perovskite quality is attributed to the surface traps, which is also consistent with slow increase of photocurrent observed in current–time ( I – t ) scan shown in Figure S9 of the Supporting Information . It was also reported that the hysteresis is related to the energy level alignment at ETL/perovskite interface, which in turn is affected by the presence of deep trap states . In addition to the reduction in the interface trap density, improvements in the conductivity of SnO 2 may also contribute to reduced hysteresis .…”
Section: The Summary Of Parameters Of Devices and Films For Differentsupporting
confidence: 84%
“…This is similar to the case of PCBM ETL. Such a dramatic suppression of the hysteresis may come from the improved electron transport due to the strong electron-accepting ability of 2a and 2b, resulting in suppressed charge accumulation at the perovskite/ITO interface [49,50]. Therefore, these results along with the comparable PCE to PCBM reveal the promising applications of 2a and 2b in PSCs.…”
Section: Applications Inmentioning
confidence: 93%
“…Shallow and delocalized Pb‐Cl antisite defects are seen for the PbCl 2 ‐terminated interface (right). Reproduced with permission . Copyright 2017, The American Association for the Advancement of Science.…”
Section: Passivation Of Carrier Transport Layer (Ctl)mentioning
confidence: 99%
“…Red dashed lines represent the trap states. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Passivation Of Carrier Transport Layer (Ctl)mentioning
confidence: 99%
See 1 more Smart Citation